Estimation of biomass allocation during crop cycle in two sweet potato varieties - Pérez Pazos, Jazmín Vanessa; Martínez Figueroa, Remberto Rafael; Pérez Pastor, José Luis; Pastrana Vargas, Iván Javier; Cordero Cordero, Carina Cecilia; Rosero Alpala, Elvia Amparo (‎‎Corporación colombiana de investigación agropecuaria - AGROSAVIA, 2019)
A quantitative approach to understand plant development is the analysis of growth through the monitoring of biomass allocation by determining parameters such as dry matter and foliar area over time, these variables allow to obtain derived measures such as growth rates that allow obtaining information on the state of the crop (Poorter et al., 2012; Pérez-Harguindeguy et al., 2013). Taking into account that the new varieties offer different advantages among which higher yields are found, the characteriacion by means of growth indexes is an opportunity to identify the management strategies that allow to obtain their maximum potential. This research was carried out in two varieties Corpoica Aurora and Corpoica Ambarina with the objective of comparing the growth and biomass allocation during the crop cycle. The variables leaf area and dry matter of leaves, stems and roots were evaluated and growth rates were obtained.